2010
DOI: 10.1016/j.brainres.2010.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of Sorting Nexin 2 and androgen receptor in the song system of juvenile zebra finches

Abstract: Mechanisms regulating sexual differentiation of the zebra finch song system appear to include both genetic and hormonal factors. Sorting Nexin 2 (SNX2), which is involved in trafficking proteins between cellular membranes, and androgen receptor (AR) mRNA are both increased in song control nuclei of juvenile males compared to females. Here, in situ hybridization for SNX2 and immunohistochemistry for AR were used to evaluate these sexual dimorphisms in more detail. Estimates of the total number of HVC cells expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Males had a significantly higher degree of co-localization (AR cells expressing HSD17B4) in HVC in comparison to females. These results mirror those found with sorting nexin 2 and ribosomal proteins L17 and L37 (Tang & Wade, 2010; Wu et al, 2010), and collectively point to the possibility that the co-localization of a variety of Z-chromosome genes and AR may be important for the masculinization of the song system. However, E2 treatments had no effect on the extent of the co-localization in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Males had a significantly higher degree of co-localization (AR cells expressing HSD17B4) in HVC in comparison to females. These results mirror those found with sorting nexin 2 and ribosomal proteins L17 and L37 (Tang & Wade, 2010; Wu et al, 2010), and collectively point to the possibility that the co-localization of a variety of Z-chromosome genes and AR may be important for the masculinization of the song system. However, E2 treatments had no effect on the extent of the co-localization in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…This is surprising, since earlier work documented a sex difference in AR protein expression in Area X at this same age (Wu, et al, 2010). However, mismatches between mRNA and protein expression do occur(Chen et al, 2002; Greenbaum et al, 2003), and Wu and colleagues (2010) quantified the total number of cells expressing AR-ir rather than the number within a specified area as we did. Another study (Kim, et al, 2004) measured mRNA and also found a sex difference.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Western blot was used to test specificity of the antibody N-20 (sc-816, Santa Cruz Biotech) a polyclonal antibody raised against a peptide mapping at the N-terminus of AR of human origin that has been used in zebra finches, quail and chickens (Kharwar and Haldar, 2011; Shaw and Kennedy, 2002; Tang and Wade, 2010, 2011; Wu et al, 2010). Micropunched tissue from starling and mouse was homogenized with ice-cold lysis buffer (1.0 mL/100 mg of tissue) in pre-chilled centrifuge tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Omission of the primary AR antibody also eliminated labeling in zebra finch brain (Wu et al, 2010). Additional tests were conducted for this set of studies.…”
Section: Methodsmentioning
confidence: 99%